The Flush Model: A Novel Framework to Manage Surgeons’ Mental Fatigue and Cognitive Load - Pierrick Laulan, PhD; Matthieu L. G. Fernandez, MSc; Emeric Abet, MD; Jérôme Dimet, MD; Ulrike Rimmele, PhD (Annals of Surgery Open)
Background:. Mental fatigue significantly impairs surgeons’ cognitive performance, compromising patient safety. However, surgical practice lacks an integrated framework to understand and mitigate this cognitive strain effectively. Conceptual Model:. We propose adapting the Flush model, initially developed for endurance sports, to surgical settings. This model conceptualizes mental fatigue through a dynamic analogy of a water tank composed of 4 main components: perceived fatigue (ballcock), fatigue accumulation (filling rate), fatigue recovery (drain rate), and a safety margin (security reserve). We detail how intrinsic cognitive load, extraneous stressors, physiological and psychological factors, and circadian influences collectively drive mental fatigue accumulation. Clinical Implications:. The Flush model clarifies how mental fatigue fluctuates during surgical procedures and highlights practical recovery methods such as brief mindfulness interventions, microbreaks, cognitive offloading, and ergonomics adjustments. It emphasizes maintaining a cognitive safety reserve to safeguard against errors during critical surgical phases, providing surgeons with actionable strategies to manage fatigue in real time. Future Directions:. We recommend empirical validation through real-time monitoring using physiological measures (eg, heart-rate variability, pupillometry) coupled with subjective assessments (eg, NASA Task Load Index, Surgery Task Load Index). Integrating Flush principles into surgical training, simulation programs, and institutional policies could foster a culture prioritizing cognitive performance and patient safety. Conclusions:. The Flush model provides a comprehensive, intuitive framework for understanding and addressing surgeons’ mental fatigue. Its implementation promises to enhance cognitive resilience, reduce surgical errors, and improve both patient outcomes and surgeon well-being.